Urinary Excretion of Cyanidin Glucosides and Glucuronides in Healthy Humans After Elderberry Juice Ingestion. Issue 5 (1st December 2004) - Bitsch, Roland; Netzel, Michael; Sonntag, Susanne; Strass, Gabriele; Frank, Thomas; Bitsch, Irmgard
Abstract : In a pilot study with 6 females and 1 male, the metabolism of various cyanidin glucosides after oral administration of elderberry juice was investigated. The anthocyanin metabolites were detected in urinary excretion. After ingestion of a bolus quantity of3.57 g total anthocyanins in a150 mL elderberry juice concentrate, 0.053 % of the administered dose was excreted in urine as glucosidically bound cyanidins within the first 5 hours. Only0.003 % of the ingested anthocyanin glucosides was excreted as cyanidin glucuronide, suggesting that this conversion step might be of minor importance in urinary excretion.